Materials and Substances Relating to Polyions and Substance Delivery [ChargeSwitchTM & EasyplexTM DNA Isolation Technology] US Patent 7319004 B2 - Garry Harper (2008)
Materials and methods relating to polyions and substance delivery US 7319004 B2ABSTRACTMaterials and method are disclose for delivering a desired substance to a target site, using a layered carrier in which the carrier and the substance together form at least three layers which associate by ionic interaction at the first pH, where at least one layer comprises a charge switch material which comprises an ionisable group and which has a positive charge at a first pH and a charge which is less positive, neutral or negative at a second pH, at least one layer comprises a polyionic polymer which is negatively charged at the first pH and at least one layer comprises the desired substance. Preferred carriers are based on the charge switch material poly Bis-Tris and the polyionic polymer polyacrylic acid.